When to Deliver Women with Diabetes in Pregnancy? - Caughey, Aaron B.; Valent, Amy M. (American Journal of Perinatology, 2016)
The prevalence of pregestational diabetes and the incidence of gestational diabetes have both increased over recent years. One component of the management of diabetes in pregnancy is the timing of delivery in the late-preterm, early-term, or full-term periods. Recent guidance from the National Institute for Child Health and Human Development, Society for Maternal-Fetal Medicine, and American College of Obstetricians and Gynecologists has lacked specificity, for example, recommending delivery for women with pregestational diabetes with poorly controlled glucose levels to be from 34 to 39 weeks' gestation. This lack of specificity is predominant because of the large holes in existing data to guide clinical practice. This article reviews existing literature regarding diabetes in pregnancy and attempts to give an analytical framework and some clearer guidance around the timing of delivery.
Keywords: diabetes; pregnancy; term; timing; induction